Accuracy of task recall for epidemiological exposure assessment to construction noise. Issue 2 (22nd January 2004) - Reeb-Whitaker, C K; Seixas, N S; Sheppard, L; Neitzel, R
Abstract : Aims: To validate the accuracy of construction worker recall of task and environment based information; and to evaluate the effect of task recall on estimates of noise exposure. Methods: A cohort of 25 construction workers recorded tasks daily and had dosimetry measurements weekly for six weeks. Worker recall of tasks reported on the daily activity cards was validated with research observations and compared directly to task recall at a six month interview. Results: The mean LEQ noise exposure level (dBA) from dosimeter measurements was 89.9 (n = 61) and 83.3 (n = 47) for carpenters and electricians, respectively. The percentage time at tasks reported during the interview was compared to that calculated from daily activity cards; only 2/22 tasks were different at the nominal 5% significance level. The accuracy, based on bias and precision, of percentage time reported for tasks from the interview was 53–100% (median 91%). For carpenters, the difference in noise estimates derived from activity cards (mean 91.9 dBA) was not different from those derived from the questionnaire (mean 91.7 dBA). This trend held for electricians as well. For all subjects, noise estimates derived from the activity card and the questionnaire were strongly correlated with dosimetry measurements. The average difference between the noise estimate derived from the questionnaire and dosimetry measurements was 2.0 dBA, and was independent of the actual exposure level. Conclusions: Six months after tasks were performed, construction workers were able to accurately recall the percentage time they spent at various tasks. Estimates of noise exposure based on long term recall (questionnaire) were no different from estimates derived from daily activity cards and were strongly correlated with dosimetry measurements, overestimating the level on average by 2.0 dBA.